The Effectiveness of Median Nerve Mobilization in Patients with Cervical Radiculopathy: A Systematic Review - Robin Mathew, P.J.; Karishma, Chauhan; Jeffery, Samuel (INTI International University, 2025)
As cervical radiculopathy incidence is on the increase, largely due to aging populations and lifestyle-related issues, its conservative management relies heavily on physiotherapy. Median nerve mobilization has emerged as a potential modality for pain reduction, improved functional outcomes, and enhancement of nerve mobility in patients with CR. The systematic review considered the literature published between 2014 and 2025, including 10 high-quality studies, which comprised randomized controlled trials, systematic reviews, and one case report, that evaluated MNM alone or in combination with either conventional physiotherapy or cervical traction. Commonly, findings revealed that MNM provided a valuable addition to the standard modalities of treatment, providing significant improvements in pain reduction, cervical range of motion, muscle endurance, disability scores, and overall functional outcome, while demonstrating better tolerance and fewer side effects than pharmacological intervention. In general, MNM appears to be safe, non-invasive, and effective in the conservative management of cervical radiculopathy, adding to functional independence and quality of life, although large-scale, well-standardized trials are needed to determine long-term effectiveness and the optimization of treatment packages.